2017
DOI: 10.7324/jabb.2017.50308
|View full text |Cite
|
Sign up to set email alerts
|

Glycine betaine mediated disease resistance against Sclerospora graminicola in Pearl Millet

Abstract: The present findings on Glycine betaine provides significant perception on the dynamics of pearl millet by activating the host defense responses during its interaction with the pathogen. Glycine betaine treatment to seeds at 30 mg ml -1 concentration for 6 h significantly enhanced the seed germination and seedling vigor of pearl millet in comparison with the control. Significant inhibition of sporangial sporulation, zoospore release and motility was observed at 30 mg ml -1 , even though it failed to exhibit co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…LOX also increased after CMV infection and treatment with GB and CHT. Similar results reported by Lavanya and Amruthesh [42] found that exogenous application of GB against Sclerospora graminicola in Pearl Millet inducing LOX expressions for protecting pathogen which could lead to desaturation of lipid peroxidation products by increasing membrane stability and genes involved in stress defense mechanism via the octadecanoid pathway.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…LOX also increased after CMV infection and treatment with GB and CHT. Similar results reported by Lavanya and Amruthesh [42] found that exogenous application of GB against Sclerospora graminicola in Pearl Millet inducing LOX expressions for protecting pathogen which could lead to desaturation of lipid peroxidation products by increasing membrane stability and genes involved in stress defense mechanism via the octadecanoid pathway.…”
Section: Discussionsupporting
confidence: 86%
“…In general, plants can tolerate the diseases infection through a wide range of cellular processes; (i) up-or down-regulation of different genes; (ii) changes in pathway levels of various compounds, like reactive oxygen species (ROS); (iii) stimulation of various transcription factors activity, regulation of defense genes and pathogenesis related proteins, (iv) stimulation of protective signaling enzymes and phytohormones such as SA, JA, auxins, cytokinins, abscisic acid and gibberellic acid [40,41]. The present findings show that GB and CHT can protect cucumber plants against CMV not only by the reduction of symptom and disease severity, but also by decreasing viral titer [42].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation